Pemberdayaan Kader Posyandu Dalam Pengolahan Jahe Merah Untuk Menurunkan Kadar Gula Darah - Dita Hanna Febriani; Veronica Ima Pujiastuti; Ana Setiyorini (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Empowerment of cadres in utilizing local resources to reduce blood sugar levels of residents with type 2 diabetes mellitus is one of the important things in controlling type 2 diabetes mellitus. The purpose of this community service is to empower cadres in diversifying processed ginger to reduce blood sugar levels. The implementation method is carried out in three stages. The results showed that the knowledge of cadres increased after education and demonstrations about DM management and ginger processing were carried out. The conclusion of this activity is education and demonstration to posyandu cadres in Ngabean Kulon Hamlets provides good benefits in facilitating the development of the role of cadres in efforts to increase knowledge and management of type 2 diabetes mellitus.